Cross-talk between the gut microbiota and hypothyroidism: a bidirectional two-sample Mendelian randomization study - Shi, Chao; Chen, Jie; He, Siying; Zhang, Yingying; Zhang, Yanyue; Yu, Lisha (Frontiers in Nutrition, 2024)
Background Multiple observational studies suggest a connection between the composition of the gut microbiota and hypothyroidism. However, it has yet to be determined whether the gut microbiota has a causal effect on hypothyroidism.Methods To investigate the connection between the gut microbiota and hypothyroidism, twosample Mendelian randomization was performed using data from a genome-wide association study meta-analysis (n=18,430) conducted by the MiBioGen consortium. Summary statistics for hypothyroidism (26,342 cases and 59,827 controls) were obtained using the data from the FinnGen consortium R8 release data. To investigate the causal link between the gut microbiota and hypothyroidism, various methods, including MR-Egger, weighted median, weighted model, simple model, MR-PRESSO, and inverse variance weighted (IVW), were employed.The bacteria that were causally linked to hypothyroidism in forward Mendelian randomization analysis were subjected to reverse Mendelian randomization analysis. Cochran's Q statistics were utilized to gauge the heterogeneity of the instrumental variables.3The results indicated that Akkermansia had a positive impact on hypothyroidism, with an odds ratio of 0.84 (95% CI 0.74-0.95, P = 0.01) based on the inverse variance-weighted estimates. Additionally, Anaerostipes (OR = 1.17, 95% CI 1.01-1.36, P = 0.04), Butyrivibrio (OR = 0.93, 95% CI 0.88-0.99, P = 0.02), Holdemania (OR = 0.89, 95% CI 0.81-0.99, P= 0.03), Intestinimonas (OR = 1.13, 95% CI 1.02-1.26, P = 0.03), Ruminiclostridium5 (OR = 1.19, 95% CI 1.01-1.41, P = 0.04), and Ruminococcaceae UCG-011 (OR = 0.91, 95% CI 0.84-0.99, P = 0.03) were identified. The gut microbiota was not significantly affected by hypothyroidism, as indicated by the results of the reverse MR analysis. There was no significant variation in the instrumental variables or horizontal pleiotropy. 4 Conclusions The findings of this study using two-sample Mendelian randomization indicate a causal relationship between Akkermansia and hypothyroidism. Increased Akkermansia inhibits the onset and progression of hypothyroidism. Additional randomized controlled experiments are necessary to elucidate the beneficial impact of probiotics on hypothyroidism and their distinct protective mechanisms.